(untitled) (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
Competence in the use of Information Communication Technology (ICT) is a buzz word today given the fact that ICTs have impacted almost all sectors of the global society. Most employers, for example, require people who possess skills in certain ICT when they look for potential employees. Thus, Department of Education‘s White paper on e-Education indicates “The ICT revolution has had impact of curriculum development and delivery and continues to pose new challenges for education and training systems around the world.” In this regard, schools as social institutions charged with the responsibility of developing human resources cannot overlook the need for inclusion of ICT in the process of teaching and learning so as to empower and equip learners with necessary skills that they will need to function and meet challenges awaiting them. It is against this background that educational researchers are advocating the integration of ICT in the learning and teaching of history in particular and other subjects in general. The purpose of this article, therefore, is to discuss the implications of the turn to ICT for history teaching and learning with particular reference to Windows Movie Maker and history teaching. The essay will mainly focus on: opportunities, costs, the implications on history teachers’ professional practice and challenges in integrating Windows Movie Maker into history education. Possible solutions to the challenges will also be emphasised.